The Effect of SSCS Learning Model on the Mathematical Problem Solving Ability of Junior High School Students, Kampar Regency - Muhammad Syafri; Zulkarnain Zulkarnain; Maimunah Maimunah (Journal of Educational Sciences, 2020)
Problem solving ability is a very important ability possessed by students in solving school mathematics problems. The purpose of this study is to determine the mathematical problem solving ability of students who use the Search, Solve, Create and Share (SSCS) learning model and the students who study with conventional learning. This research was a quasi-experimental study with a non equivalent control group design. The subjects in this study were all Kampar Junior High School students. The analysis technique used was the One-Way Anova Test and Two-Way Anova Test. The results showed the mathematical problem solving ability of students who learned to use the SSCS model was better than students who learned to use conventional learning models. However, there is no interaction observed between SSCS learning model and students mathematical problem solving ability (KPMM) level on students' mathematical problem solving abilities in Kampar Regency